Consistent social odor representation across 7 languages: the Social Odor Scale translation and validation - Cecchetto, Cinzia; Leleu, Arnaud; Calce, Roberta P.; Arnhardt, Sally; Parma, Valentina; de Groot, Jasper H.B.; Freiherr, Jessica; Gentili, Claudio; Zou, Laiquan; Thunell, Evelina; Fischmeister, Florian Ph S.; Rekow, Diane; et al. (Chemical Senses, 2024)
The Social Odor Scale (SOS) is a 12-item questionnaire initially developed and validated in Italian and German to investigate self-reported awareness of social odors, which are odors emanating from the human body that convey diverse information and evoke various emotional responses. The scale includes a total score and 3 subscales representing social odors in the respective categories: romantic partner, familiar, and strangers. Here, we aimed to (i) replicate the validation of the Italian and German versions of the SOS, (ii) translate and validate the SOS into multiple additional languages (French, English, Dutch, Swedish, Chinese), and (iii) explore whether the factor structure of each translated version aligns with the original versions. Confirmatory Factor Analysis (CFA) supported the scale's structure, yielding a good fit across all languages. Notable differences in SOS mean scores were observed among the different languages: Swedish participants exhibited lower social odor awareness compared to the other groups, whereas Chinese participants reported higher social odor awareness compared to Dutch and Swedish participants. Furthermore, SOS scores correlated with respondents' geographical location, with higher (i.e. northern) latitudes linked to lower social odor awareness. These results corroborate the SOS as a valid and reliable instrument, especially for the SOS total score and the Familiar and Partner factors, emphasizing the influence of individual and geographic factors on social odor awareness.
CRIS-Team Scopus Importer:2024-10-18
Keywords: body odors; culture; odor awareness; olfaction; social odors